2017
DOI: 10.1080/1067828x.2017.1299656
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Racial/Ethnic Discrimination on Substance Use Among Youths Living in the Cherokee Nation

Abstract: We examined frequency and intensity of racial/ethnic discrimination and the longitudinal relationship to substance use. The sample included (N = 1,421) American Indian, American Indian and White, and White adolescents. A high frequency of perceived racial discrimination was associated with an increased risk for heavy alcohol use, prescription drug misuse, and other illicit drug use. Experiences of perceived racial discrimination high in intensity were associated with further increased risk of prescription drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…For example, compared to white adolescents of the same age, Latino and black adolescents were at increased risk for opioid misuse, with Hispanic adolescents twice as likely as white peers to misuse opioids [ 63 ]. In addition, Native American children who had a high perceived frequency of racial discrimination were more likely to misuse prescription drugs [ 64 ]. Considering gender identity as a risk factor, transgender youth were more likely to develop SUD than their cisgender peers [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, compared to white adolescents of the same age, Latino and black adolescents were at increased risk for opioid misuse, with Hispanic adolescents twice as likely as white peers to misuse opioids [ 63 ]. In addition, Native American children who had a high perceived frequency of racial discrimination were more likely to misuse prescription drugs [ 64 ]. Considering gender identity as a risk factor, transgender youth were more likely to develop SUD than their cisgender peers [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…A domain of interpersonal stress that has received a great deal of attention over the past decade is perceived discrimination (Pascoe & Smart Richman, 2009; Unger, 2015). Among youth, the impact of perceived discrimination on substance use outcomes has been examined based on specific attributes, such as race or ethnicity (Acosta, Hospital, Graziano, Morris, & Wagner, 2015; Basáñez, Unger, Soto, Crano, & Baezconde-Garbanati 2013; Gibbons et al, 2012; Garrett, Livingston, Livingston, & Komro, 2017; Sanders-Phillips et al, 2014), weight or physical appearance (Madkour et al, 2015), and sexual orientation (Grollman, 2012; Thoma & Huebner, 2013). Although the most robust effect has been found for race-based discrimination (Grollman, 2012; Madkour et al, 2015; Thoma & Huebner, 2013).…”
mentioning
confidence: 99%
“…Several researchers have found associations between direct, personal experiences of racism and substance use among people of color. In a study of 1,421 Native American, White, and biracial (Native American and White) youth from the Cherokee Nation, researchers found that those who experienced moderate frequencies of discrimination had greater odds of using marijuana and other drugs (Garrett et al, 2017). Additionally, researchers surveyed university students of color and determined that for every one standard deviation increase in microaggression scores, regular marijuana use increased by 31% (Pro et al, 2018).…”
Section: Direct Experiences Of Racism Negative Affect and Substancementioning
confidence: 99%